Effect of pre-experimental maintenance care duration on the development of gingivitis in a partial mouth experimental gingivitis model - Van der Weijden, G A; Timmerman, M F; Danser, M M; Nijboer, A; Saxton, C A; Van der Velden, U (Journal of periodontal research, 1994)
The present study was designed to evaluate if different periods of supervised oral hygiene prior to the experimental gingivitis trial have an effect on the amount of inflammation which develops in the 'toothshield' model. Two groups were compared. One group (Group A) was supervised over a 5-month period before experimental gingivitis. Six months later Group A participated in a second trial, this time receiving only a 1-month pretrial. A second group (Group B) which served as a control was supervised over a pre-trial period of 1-month prior to the start of the experimental gingivitis phase. During the pre-trial period all subjects undertook a regime of vigorous oral hygiene which included polishing of the test quadrant in the upper jaw and supervised subgingival brushing, interdental taping or the use of toothpicks. The presence of plaque and bleeding were assessed. Following the pre-trial period all plaque control measures in the experimental area were prevented during oral hygiene periods by the temporary placement of soft, loosely fitting vinyl toothshield guard. During this period they accumulated plaque rapidly and developed a generalized gingivitis. The results of this study indicate that, irrespective of the length of the pretrial period, subjects by group develop a comparable mean level of plaque and gingival bleeding. However, the extent to which gingivitis develops differs among individuals and was for a number of subjects not consistent. Therefore, in designing an experimental gingivitis trial care should be taken to include a sufficient number of subjects to account for individual variation.